AGBL4 promotes malignant progression of glioblastoma via modulation of MMP-1 and inflammatory pathways - Zhang, Shuai; Cheng, Lilin; Su, Yandong; Qian, Zhongrun; Wang, Zhen; Chen, Chao; Li, Rong; Zhang, Aikang; He, Jiawei; Mao, Jiangxin; Wang, Hongxiang; Chen, Juxiang (Frontiers in Immunology, 2024)
Glioblastoma multiforme (GBM), the most common primary malignant brain tumor, is notorious for its aggressive growth and dismal prognosis. This study aimed to elucidate the molecular underpinnings of GBM, particularly focusing on the role of AGBL4 and its connection to inflammatory pathways, to discover viable therapeutic targets. Through single-cell sequencing, we identified a significant upregulation of AGBL4 in GBM, correlating with adverse clinical outcomes.Functional assays demonstrated that AGBL4 knockdown inhibited, while its overexpression facilitated, GBM cell proliferation, migration, and invasion, and also influenced inflammatory response pathways. Further investigation revealed that AGBL4 exerts its oncogenic efforts through modulation of MMP-1, establishing a novel regulatory axis critical for GBM progression and inflammation. Therefore, both AGBL4 and MMP-1 may be pivotal molecular targets, offering new avenues for targeted therapy in GBM management.